Sustainability Accounting as The Key to Success for Startup Companies: Literature Review - Zulkarnaen, Have (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research examines accounting strategies to encourage sustainability in technology startups. The main focus is how the integration of environmental, social and governance (ESG) aspects in accounting practices can increase transparency, accountability and relationships with stakeholders which are useful for the success of Start Up companies. Technology startup companies often face limited capital, resources and challenges in implementing sustainability accounting systems, this research shows that the benefits obtained are very significant. Through the literature review method, this research identifies various theoretical approaches such as sustainability accounting theory, stakeholder theory, triple bottom line theory, legitimacy theory, and institutional theory. Each theory provides a different perspective on the importance of implementing good accounting and how to integrate sustainability in accounting practice. This research also highlights key challenges such as limited resources, the risk of greenwashing, and the lack of standardized reporting standards. However, opportunities for innovation and development of new solutions are also wide open. Tech startups can leverage technologies such as blockchain and artificial intelligence to improve the efficiency and accuracy of sustainability reporting. In addition, external support through green funding programs and government incentives can help overcome resource constraints. In conclusion, implementing sustainability accounting strategies can provide long-term benefits for technology startups, including increased operational efficiency, reduced environmental risks, and gained legitimacy from society and investors. To overcome existing challenges, it is recommended that technology startups leverage innovative technologies, seek external support, increase education and training in sustainability accounting, and develop standards and guidelines that suit their needs. With the right approach, technology startups can strike a balance between sustainability goals and business growth, and make a significant contribution to a more sustainable future.